Ответы и объяснения

2014-04-15T13:10:04+00:00
(6x+3)(9-x)=0
54x-6x^2+27-3x=0
-6x^2+51x+27=0  | разделим на(-3)
2x^2-17x-9=0
D=289+72=361
x=(17+-√361)/4=(17+-19)/4
x1=(17+19)/4=9            x2=(17-19)/4=-0,5


второй номер на фотке


{3x-2y=16
{4x+y=3

{3x-2y=16
{y=3-4x

{3x-6+8x=16
{y=3-4x

11x=22
x=2
y=3-8
y=-5
Ответ:(2;-5)


{2x+6>4x+6
{4x+10<0

{2x<0
{4x<-10

{x<0
{x<-2,5
Ответ: x<-2,5

5 номер на фотке

3\sqrt{2}= \sqrt{9*2}= \sqrt{18}  4= \sqrt{16}
В порядке возрастания  \sqrt{15} ;  4;  3\sqrt{2}

c-16c^3=c(1-16c^2)=c(1+4c)(1-4c)